The Horn Technique for Nasal Tip Support in Rhinoplasty - Barboza,Luiz Carlos de Melo (2021)
Abstract Introduction The predictability of nasal tip projection and rotation after aesthetic surgery is a challenge. Tongue-in-groove (TIG) is an effective technique to control tip projection and rotation, but there may be a small loss of projection and rotation of the tip lobe due to lack of support between the anterior septal angle and the domus, since this region is sustained by medial crusts suture-linked and interdomus sutures. Objective To describe a new surgery technique in an attempt to correct the lack of support for the nasal tip after lowering the nasal dorsum. Methods The horn technique consists in preserving a square of cartilage during the removal of the nasal dorsum and septum excess in patients with long and projected nose. This piece will give greater support to the TIG technique and greater predictability of the rotation and projection of the nasal tip. Results Between 2016 and 2018, 50 patients with long and projected noses were submitted to the “horn technique” surgery. They were submitted to the TIG technique associated to the horn technique. A retrospective review of the preoperative and postoperative photographs (3 months to 1 year) of these patients treated with the horn technique were analyzed and showed better support of the nasal tip. Conclusion The horn technique provides greater support to the projection and rotation of rhinoplasties in patients with long and projected nose.